ENHANCING STUDENTS’ SPEAKING SKILL THROUGH LINGUISTIC LANDSCAPE-BASED PEDAGOGICAL MODEL: AN EXPERIMENTAL STUDY ON THE FIFTH SEMESTER OF EFL STUDENTS - Putra, Harjuli Surya (Journal of Language, Literature and Teaching, 2025)
Linguistic Landscape-Based Pedagogical Model is a fruitful material for language teaching in real-life situations in L2 speaking class. The use of various city signs and urban symbols in a broader social context in language teaching engages the students into a productive learning situation. This study is an attempt to investigate how Linguistic Landscape improve students’ speaking skill on the fifth semester students of English Study at STBA-PIA Medan. To achieve the objectives of the current study, this study applies experimental design using quasi-experimental design. By using the data obtained, it was found that there was significant improvement for the experimental group in the post-test. There are 40% of students belonging to excellent category, 30% students belonging to good category, and 30% students belonging to fair category. Further, this research revealed three significant benefits of using Linguistic Landscape for language teaching. First, using Linguistic Landscape as a teaching resource in the classroom, the students will be more aware of their Linguistic Landscape. Second, the students will perceive the use of LLs in the classroom positively improved their language skills. Third, LLs will provide the students with the best opportunity to increase their creativity, critical thinking, and literacy skills.  Keywords: EFL students, language teaching, linguistic landscape, signs, speaking skill